The Concept of Translation and Characteristics of Features (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses the theoretical foundations of translation feature. The concept of translation, literary translation, characteristics and features of translation in the works of different authors. The translation plays important role in the formation of the culture of peoples, raising the spiritual, moral, intellectual level of peoples. It is literary translation that gives us the opportunity to master the most beautiful aspects of world cultures, as well as analyze the negative aspects of world cultures.